"We can never close the book and say, 'We'll continue next week'" – The rhythms of cooking and learning to cook in Swedish Home economics. (27th May 2022) - Bohm, Ingela
ABSTRACT: The Swedish school subject Home Economics (HE) covers complex content to do with cooking and sustainable development, but is allocated relatively few hours. I draw on observations of HE lessons and interviews with teachers to show how experiences of time poverty can be conceptualized as arrhythmia in relation to the requirements of the curriculum, scheduling, cultural expectations, and the unpredictable nature of student cooking. By viewing cooking and learning to cook as sets of rhythms, I illuminate the disjoint between the mathematical rhythms of scheduling and recipes on the one hand and the visceral rhythms of students and food on the other. As teachers struggle to translate the vague knowledge goals and linear progression of the syllabus into the cyclical rhythms of meal-centered lessons where cooking is organized as a group activity, they prioritize time-consuming recipes and cleaning over reasoning around sustainability, which may contribute to a feeling of not keeping up with the contents of the syllabus.